2014
DOI: 10.20533/ijcdse.2042.6364.2014.0277
|View full text |Cite
|
Sign up to set email alerts
|

Presenting a Model That Leads School Leaders’ Empowerment

Abstract: The purpose of this study was to present a model that leads school leaders' empowerment, utilizing the following variables: resources to reward, information management, instructional leadership, and knowledge of technology. A survey was sent to school leaders in the United States who were trained to use IBM Change Toolkit software. 304 school leaders answered this survey. A structural equation model was used to create the model. The model shows that the major contributors of school leaders' empowerment are ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A study (T. Shah et al, 2014) found that knowledge of technology, adequacy of resources, and motivations are among the factors that affect the empowerment of school leaders in the United States of America.…”
Section: Theoretical Framework and Previous Studiesmentioning
confidence: 99%
“…A study (T. Shah et al, 2014) found that knowledge of technology, adequacy of resources, and motivations are among the factors that affect the empowerment of school leaders in the United States of America.…”
Section: Theoretical Framework and Previous Studiesmentioning
confidence: 99%
“…Psychological empowerment is defined by Spreitzer (1992) as "the feeling of having control over one's destiny" (Shah, Riaz, Kelly, & Morote, 2014, p. 2000. Four dimensions of psychological empowerment suggested by Spreitzer (1995) include meaning, competence, self-determination, and impact (Shah et al 2014).…”
Section: Psychological Empowerment Theorymentioning
confidence: 99%
“…Psychological empowerment is defined by Spreitzer (1992) as "the feeling of having control over one's destiny" (Shah, Riaz, Kelly, & Morote, 2014, p. 2000. Four dimensions of psychological empowerment suggested by Spreitzer (1995) include meaning, competence, self-determination, and impact (Shah et al 2014). For principals, feelings of psychological empowerment may emerge from the selfless motivations of educating youths, sufficient background and training in education and educational leadership, and a feeling of confidence in one's ability to make a difference, as well as many other areas (Houghton &Yoho, 2005 andShah, et al 2014).…”
Section: Psychological Empowerment Theorymentioning
confidence: 99%